Ad Hoc Wireless Routing With Density Based Probabilistic Algorithm For Mobile Wireless Networks With Non-Uniform Node Distribution - Ong , Hean Loong (2010)
This thesis introduced three custom mobility scenanos based on the different density configurations that mimic urban areas, highways or disaster area.Kajian ini mengemukakan tiga jenis corak gerakan nod-nod rangkaian tanpa wayar muda.1 alih yang merupai situasi di persekitaran bandar, lebuhraya atau bencana alam.